The Effect of Trust and Knowledge Towards Farmer’s Decision for Paying Zakat With Religiosity as Moderating Variable (Deleng Pokhison District Case Study) - Yenni Samri Juliati Nasution; Sudirman Suparmin; Yana Suhaina (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to analyze the effect of trust and knowledge towards farmer’s decision for paying zakat in Baitul Mal with religiosity as moderating variable. This study used quantitative method. Total population of this study is 2185. With random sampling technique, the sample for this study produce 100 respondents. Analysis method that was used is Moderate Regression Analysis (MRA). Data processed with SPSS 22. The result of this study show that partially trust have positive and significant effects towards farmer’s decision for paying zakat (71,5%) dan partially knowledge have no effects towards farmer’s decision for paying zakat (0,9%). Trust and knowledge simultaneously have positive and significant effects towards farmer’s decision for paying zakat with significant value 0,0002,47. Trust and knowledge have positive effects towards farmer’s decision for paying zakat in Baitul Mal with religiosity as moderating variable.